Soil chemical and physical properties with rice straw management during fallow period (2012)
Proper method and timing of incorporating farm biomass such as rice straw into the soil is vital to ensure soil organic matter (SOM) build up. Two field experiments were conducted in two sites with different levels of soil organic matter (SOM) to determine the appropriate means of managing the biomass left after harvest of rice crops during the fallow period. The effect of mowing rice stubbles and incorporation of rice straws left after harvest during the fallow period were determined. The effects of different land preparation methods and fertilizer management were also assessed, based on the physical and chemical properties of the soil. In general, mowing of rice stubbles and methods of land preparation have no effect on carbon-nitrogen (C :N) ratio of soil organic matter, bulk density, depth of mud, and on certain soil chemical properties. About 70% of the rice straw incorporated is composed of stubbles left after harvest and 30% from threshed rice straw. Increased C :N ratio 2 months before transplanting up to harvest time implies that the incorporated straw has not been thoroughly decomposed. Mineralizable or available nitrogen (N) tend to be lower with higher SOM level. This is due to the recalcitrant nature of SOM when conditions allow them to accumulate , such as under reduced condition in poorly drained soils. Additional inorganic N must be supplied even in soils with high SOM to offset immobilized N. The amount of straw to be incorporated and its respective N content are critical in SOM accumulation. Higher amount of straw incorporated resulted to higher SOM accumulation. Incorporation of 4-5 t ha-1 straw, which is equivalent to one season straw biomass production per hectare, was not enough to significantly change the level of SOM, as well as the physical and chemical properties of the soil. Nevertheless, continuous recycling and incorporation of rice straw in soil during fallow period may lead to the improvement of soil properties over the long-term.